2019
DOI: 10.1093/annonc/mdw180
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with advanced prostate cancer: recommendations of the St Gallen Advanced Prostate Cancer Consensus Conference (APCCC) 2015

Abstract: advanced prostate cancer (APC) management. The successful registration of several drugs for castration-resistant prostate cancer and the recent studies of chemo-hormonal therapy in men with castration-naïve prostate cancer have led to considerable uncertainty as to the best treatment choices, sequence of treatment options and appropriate patient selection. Management recommendations based on expert opinion, and not based on a critical review of the available evidence, are presented. The various recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 68 publications
(78 reference statements)
0
28
1
4
Order By: Relevance
“…35 AR plays an important role in the treatment of mCRPC. 6 Recently, one study reported that members of the 14-3-3 family play an important role in the development and progression of PCa by regulating the transcription of PSA through the AR. 8 14-3-3ε belongs to the 14-3-3 family, which was first identified in mammalian brain tissues by Moor and Perez in 1968.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 AR plays an important role in the treatment of mCRPC. 6 Recently, one study reported that members of the 14-3-3 family play an important role in the development and progression of PCa by regulating the transcription of PSA through the AR. 8 14-3-3ε belongs to the 14-3-3 family, which was first identified in mammalian brain tissues by Moor and Perez in 1968.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, treatment with androgen ablation eventually leads to AIPC. 5 Although the androgen receptor (AR) is an effective way to treat metastatic castrate-resistant prostate cancer (mCRPC), 6 29,430 people died of PCa in the USA in 2018. 7 AR is a ligand-activated transcription factor that regulates numerous target genes, including prostate-specific antigen (PSA).…”
Section: Introductionmentioning
confidence: 99%
“…CAB in the third-line is recommended by 73% of the APCCC panel in a majority of patients, while 24% recommended it in a minority of selected patients [15]. Recommendations of fourth-line and beyond therapy were not given.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In general, ADT is achieved by surgery, drug-based monotherapy, or combined androgen blockade (CAB). [3][4][5][6] ADT results in a marked decrease in the prostate-specific antigen (PSA) level and shows a good tumor reduction effect in most cases. 7 However, the PSA may be found to gradually increase even when the testosterone value is at a castration level.…”
Section: Introductionmentioning
confidence: 99%